The transformative role of education sponsorship program among female Orphaned and Vulnerable Children (OVC) in Uganda - Zhang Xiuzi (2017)
The purpose of the current study was to explore the transformative role of education sponsorship program provided by Concern for the Girl Child (CGC) to female orphaned and vulnerable children in Uganda. The specific objectives of this study were (i) to explore aspects of OVC’s agency that have been developed by the education sponsorship program; (ii) to evaluate how the CGC education sponsorship program has facilitated the development of OVC’s agency; (iii) to assess the challenges that OVC experienced which undermined the development of their agency. Data were collected by the means of in-depth interviews with current and past Concern for the Girl Child (CGC) beneficiaries and with key informant interviews with CGC staff members as well as contact teachers in the program schools. Data analysis was facilitated by inductive coding and the Capability Approach (CA) theoretical framework. Concern for the Girl Child (CGC), is a local Non Governmental Organization (NGO) that operates in Kampala city and Luwero district, Uganda. The study findings show that the CGC education sponsorship program had developed their personal agency that manifested in increased self-esteem; the ability to explicate alternatives of choices; being responsible for their personal choices and family; and taking actions to make changes for others. CGC facilitated the development of agency among the sponsored female OVC by encouraging them to make critical choices; assigning challenging tasks to beneficiaries, allowing and welcoming beneficiaries’ voices in decision making, and cultivating positive relationships with beneficiaries. However the CGC education sponsorship program experiences some challenges which undermined the full development of their agency. These findings suggest important implications for social work practice, social work education, policy development and further research.